World Economic Outlook, April 2018 : Cyclical Upswing, Structural Change. (World Economic Outlook; World Economic Outlook ;, 2018)
This report describes the world economic outlook as of April 2018, projecting that advanced economies will continue to expand above their potential growth rates before decelerating, while growth in emerging markets in developing economies will rise before leveling off. It details global prospects and policies, including risks to the forecast, and essential determinants of long-term economic growth: labor force participation in advanced economies, the declining share of manufacturing jobs globally and in advanced economies, and the process through which innovative activity and technological knowledge spread across national borders.